2012
DOI: 10.1111/j.1365-2826.2012.02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Contact Differentially Modulates Central and Peripheral Oxytocin in Rat Pups During a Brief Regime of Mother–Pup Interaction that Induces a Filial Huddling Preference

Abstract: Central oxytocin mediates the acquisition of a filial preference for maternal odour in rat pups, manifested by their huddling preferences. The present study was designed to examine whether maternal care modulates oxytocin concentrations in rat pups and, if so, how different types of maternal contact are associated with the pups’ oxytocin concentrations. Pairs of 14-day-old littermates were removed from their home cage for 1 h and then placed with a lactating foster mother for 2 h, or they remained isolated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 88 publications
(158 reference statements)
7
57
0
Order By: Relevance
“…On the other hand, OT is known to be involved in the pupmother attachment [2]. Previous works report that maternal care, such as the presence and tactile stimuli from mothers may modulate OT concentrations in rat pups [2,3], similarly to what is seen in our study: pups receiving higher licking frequencies from the mother (HL) showed higher basal plasma OT levels.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, OT is known to be involved in the pupmother attachment [2]. Previous works report that maternal care, such as the presence and tactile stimuli from mothers may modulate OT concentrations in rat pups [2,3], similarly to what is seen in our study: pups receiving higher licking frequencies from the mother (HL) showed higher basal plasma OT levels.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, OT is known to be involved in the pup-mother attachment [2]. Previous works report that maternal care, such as the presence and tactile stimuli from mothers may modulate OT concentrations in rat pups [2,3], similarly to what is seen in our study: pups receiving higher licking frequencies from the mother (HL) showed higher basal plasma OT levels.…”
Section: Discussionsupporting
confidence: 89%
“…Neuroendocrine aspects of this attachment have been reported, such as the participation of the hormone oxytocin (OT), related to affiliative behaviors [2,3]. In humans, disturbances in the mother-infant relationship are a risk factor for psychiatric disorders such as anxiety and depression in adulthood [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis in which development shines light on the 'Dark Matter of Social Neuroscience', or the unclarified neural mechanisms between social sensory inputs and social behavior outputs (Insel, 2010). (a) During developmental sensitive periods, parental nurturing (Kojima et al, 2012;Weisman et al, 2012) and/or sensory inputs (Zheng et al, 2014) drive the activity of the PVN resulting in increased release of oxytocin. This oxytocin can regulate multi-sensory plasticity in the neocortex.…”
Section: Gene By Environment Interactionsmentioning
confidence: 99%
“…Mogi et al (2011) report that oxytocin content is lower in the cingulate cortex of rats at postnatal day 14 when separated from their mother. Oxytocin responds to maternal separation and skin-to-skin contact in pre-weanling rats (Kojima et al, 2012). Oxytocin concentrations were sampled from pre-weanling rat hypothalamus and blood at several time points during a separation and reunion paradigm with a foster mother, which in previous studies elicits a huddling preference in the pups.…”
Section: Behavioral Influence During Developmentmentioning
confidence: 99%